2014
DOI: 10.1111/apt.12616
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: inflammatory bowel disease in the elderly

Abstract: SUMMARY BackgroundElderly patients represent an increasing proportion of the inflammatory bowel disease (IBD) population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
113
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 169 publications
(336 reference statements)
4
113
0
1
Order By: Relevance
“…The upper GI tract location of CD is also more often in young patients. Only 10-15% of the cases with CD appear in patients older than 60 years [18]. In the majority of the published cases, CeD preceded the diagnosis of CD [11,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…The upper GI tract location of CD is also more often in young patients. Only 10-15% of the cases with CD appear in patients older than 60 years [18]. In the majority of the published cases, CeD preceded the diagnosis of CD [11,12,19].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][11][12][13][14] Previously, patients older than age >50 years were not considered to be candidates for iPaa because advanced age was thought to be the primary driver of greater complications and worse functional outcomes. 15 more recent studies, however, have shown that complication rates and quality of life after iPaa in selected older patients (age 50-70 years) are comparable with those in younger patients. [16][17][18][19][20][21][22][23][24] this suggests that procedure type should not be dictated by age alone, but instead should be based on an evaluation of other factors associated with treatment success, such as anal sphincter integrity, comorbidities, physiologic reserve, and patient preference.…”
mentioning
confidence: 93%
“…[16][17][18][19][20][21][22][23][24] this suggests that procedure type should not be dictated by age alone, but instead should be based on an evaluation of other factors associated with treatment success, such as anal sphincter integrity, comorbidities, physiologic reserve, and patient preference. 1,15 the association between age and procedure choice for ulcerative colitis at the population level is unknown. most studies showing the safety of iPaa in older patients were published between 1996 and 2005.…”
mentioning
confidence: 99%
“…1 We know that real IBD rarely occurs in diverticulosis, 2,3 and that prevalence of diverticulosis among IBD patients (both in ulcerative colitis (UC) and in Crohn's disease (CD) colitis) seems lower than among healthy, age-matched controls. 4,5 From January 2010 to December 2012, we performed a prospective study involving six Endoscopic Centres in central-south Italy.…”
mentioning
confidence: 99%
“…E-mail: paolousai@aob.it doi:10.1111/apt.12677 SIRS, Wilder-Smith et al 1 reported that lactose and fructose intolerances are common in patients with functional gastrointestinal disorders. On the other hand, these intolerances were often present in the absence of sugar malabsorption.…”
mentioning
confidence: 99%